DAMPAK POSITIF DAN NEGATIF PENGGUNAAN INTERNET PADA KALANGAN MAHASISWA KELAS A, B, C, DAN D ANGKATAN 2021 PRODI PEND. BAHASA DAN SASTRA INDONESIA, UNIVERSITAS NUSA CENDANA - Naranto Makan Malay (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
From this in-depth observation, it can be seen that the longer the use of the internet, the more important it is as a means of student communication. Internet facilities such as e-mail, www and YM/IRC are very popular among students, both as a means of communication and as a tool to find data for other research as well as a tool to expand the relationship and introductions between internet users. In addition, the use of the internet has given rise to a new language known as the 'language of the internet'. Indeed, the language used by using the internet depends on who and with whom internet users communicate. However, although there are many benefits of using the internet, there are also negative impacts for students. For example, pornography and SPAM have become a big problem. Until now there is no effective way to avoid these negative impacts. However, because there are many positive impacts, like it or not, like it or not, we must use the internet as the fastest and most advanced means of communication at this time. As a means of communication for students, I am certain that in the future the use of the internet will become more widespread on campus, and communicating via the internet will become as popular as using the telephone. Looking at the negative and positive impacts of Audio Visual technology, especially the Internet above, it can be concluded that when compared to the negative impacts, the positive impacts are far more numerous, so it is impossible for it to be banned in Indonesia. Based on the statement from Alex Leo Z., it is clear that the Internet will not be banned from being present in Indonesia. Indeed, the negative impact for children and adolescents has been seen in the United States while other countries have not. However, because prevention is always better, it is better for the community to be prepared early on.